(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Diabetes mellitus (DM) represents one of the most common metabolic diseases in the world, with rising prevalence in recent decades. Most cases are generally classified into two major pathophysiological categories: type 1 diabetes mellitus (DM1), which progresses with absolute insulin deficiency and can be identified by genetic and pancreatic islet autoimmunity markers, and type 2 diabetes mellitus (DM2), which is the most prevalent form and involves a combination of resistance to the action of insulin with an insufficient compensatory response of insulin secretion. In the last two decades, in parallel with the increase in childhood obesity, there has also been an increase in the incidence of DM2 in young people in some populations. Other forms of diabetes may affect children and adolescents, such as monogenic diabetes (neonatal diabetes, MODY – maturity onset diabetes of the young, mitochondrial diabetes, and lipoatrophic diabetes), diabetes secondary to other pancreatic diseases, endocrinopathies, infections and cytotoxic drugs, and diabetes related to certain genetic syndromes, which may involve different treatments and prognoses. DM1 is considered an immuno-mediated disease that develops as a result of gradual destruction of insulin-producing pancreatic beta cells that eventually results in their total loss and complete dependence on exogenous insulin. Clinical presentation can occur at any age, but most patients will be diagnosed before the age of 30 years